2022
DOI: 10.21203/rs.3.rs-1792132/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical severity of SARS-CoV-2 Omicron BA.4 and BA.5 lineages in South Africa

Abstract: Omicron lineages BA.4 and BA.5 drove a fifth wave of COVID-19 cases in South Africa. We assessed the severity of BA.4/BA.5 infections using the presence/absence of the S-gene target for infections diagnosed using the TaqPath PCR assay between 1 October 2021 and 26 April 2022. We linked national COVID-19 individual-level data including case, laboratory test and hospitalisation data. We assessed severity using multivariable logistic regression comparing the risk of hospitalisation and risk of severe disease, onc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 11 publications
4
23
2
Order By: Relevance
“…While some South African studies have suggested that Omicron BA.4 and BA.5 had similar disease severity to Omicron BA.1 and BA.2 (16,21), our data indicate a lower risk of mortality in the Omicron BA.4/BA.5 wave compared to the Omicron BA.1/BA.2 wave. Immunological observations from South Africa point to considerable immune escape of Omicron BA.4 and BA.5 from Omicron BA.1 elicited immunity, but much less so in those with vaccination (15).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…While some South African studies have suggested that Omicron BA.4 and BA.5 had similar disease severity to Omicron BA.1 and BA.2 (16,21), our data indicate a lower risk of mortality in the Omicron BA.4/BA.5 wave compared to the Omicron BA.1/BA.2 wave. Immunological observations from South Africa point to considerable immune escape of Omicron BA.4 and BA.5 from Omicron BA.1 elicited immunity, but much less so in those with vaccination (15).…”
Section: Discussioncontrasting
confidence: 84%
“…Omicron sub-variants are more transmissible than previous VOCs, with greater immune escape, with BA.4/BA.5 showing reduced neutralization from antibodies induced by BA.1 infection, more so in the unvaccinated (14,15). Early data showed that Omicron BA.4/BA.5 waves had reduced severity in South Africa (16) and the United States (17).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a smaller recent study in South Africa, 9 we did not identify evidence of differential severity of infections with the BA.4/BA.5 and BA.2 lineages in either unadjusted analyses comparing all incident cases or adjusted analyses controlling for measured characteristics of cases with each lineage. Previous analyses within our study population 4 and South Africa 16 have likewise established equivalent severity of BA.1 and BA.2 infections.…”
Section: Tablesupporting
confidence: 89%
“…As BA.4/BA.5 lineages harbor the Δ69-70 amino acid deletion in the S protein, S-gene target failure (SGTF) has been proposed elsewhere as a proxy for distinguishing BA.4/BA.5 from BA.2 lineages. 9,10 Within a sample of cases KPSC randomly selected for sequencing throughout 2022, 99.6% (243/244) of BA.4 cases and 99.0% (406/410) of BA.5 cases exhibited SGTF. In contrast, SGTF did not occur in 97.8% (2,000/2,046) of BA.2 cases, validating the use of SGTF to distinguish contemporaneous infections with the BA.4/BA.5 and BA.2 lineages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation